Preparation method of CIMNP / Aln-coated Alg composite hydrogel and application of CIMNP / Aln-coated Alg composite hydrogel in bone repair
Through the preparation and application of CIMNP/Aln@Alg composite hydrogel, the problems of donor restriction, immune rejection, infection risk and long treatment cycle in bone defect treatment are solved, and stable bone repair stents and excellent mechanical properties are provided. Promotes the growth of bone cells and bone regeneration.
Patent Information
- Application Number
- CN202411165141.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-01-07
AI Technical Summary
The existing bone defect treatment methods have problems such as donor limitation, immune rejection, infection risk, long treatment cycle and high technical complexity. The formation of new bones of allogeneic bones and artificial bones is slow and the biomechanical performance is poor.
Using the preparation method of CIMNP/Aln@Alg composite hydrogel, cuttlefish ink nanoparticles and alendronate sodium are mixed into the alginate gel through cationic cross-linking to form an injectable composite hydrogel and used for Repair of mouse skull defect model provides stable scaffold structure and excellent mechanical properties.
This hydrogel has good antioxidant properties and promotes cell osteogenesis. It can simulate the natural tissue environment, provide a favorable microenvironment for bone cells, ensure the smooth progress of the bone regeneration process, and show excellent bone repair performance in the body .
Smart Images

Figure CN119258280A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of integration of traditional Chinese and western medicine and bone repair, and specifically relates to a preparation method of a CIMNP / Aln@Alg composite hydrogel and application thereof in bone repair. Background Art
[0002] Artificial bone structures made of metal materials, which are the first choice for early clinical orthopedic applications, have the potential to cause osteoporosis due to the force shielding effect between metal implants and host bones. With the development of inorganic materials with superior osteogenic activity and good biocompatibility, they can form chemical bonds between the material interface and the host bone, thereby inducing faster bone regeneration and repair. However, due to the high brittleness, low elastic modulus and mechanical strength of inorganic materials, their degradation rate does not match the growth rate of new bone tissue, which limits their wide application in clinical practice.
[0003] The current treatment of bone defects relies on autologous bone transplantation as the "gold standard", but these treatment options are prone to complications in the bone donor area and are limited by factors such as limited bone donor areas, especially in the repair of large segmental bone defects.
[0004] At present, the main problems in the treatment of bone defects are as follows: Donor limitation: Autologous bone transplantation is limited by the limited donor area, and allogeneic bone and artificial bone have source problems. Immune rejection: Allogeneic bone and artificial bone may cause immune response, increasing the risk of treatment. Infection risk: Some treatment methods have infection risks, such as needle tract infection, deep infection, etc. Long treatment cycle: Some technologies have a long treatment cycle, causing inconvenience to patients' lives. High technical complexity: Some technologies, such as vascularized fibula transplantation technology and microsurgical vascular anastomosis technology, have high technical requirements and are limited in clinical application. Slow new bone formation: Allogeneic bone and artificial bone have a slow new bone formation rate and poor biomechanical properties. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a CIMNP / Aln@Alg composite hydrogel.
[0008] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing CIMNP / Aln@Alg composite hydrogel, characterized in that: comprising:
[0009] The squid ink sac is kneaded and stirred with water until dissolved, and then filtered to obtain a suspension; the obtained suspension is centrifuged and the supernatant is taken and further centrifuged, water is added to the precipitate and stirred, and the precipitate is repeatedly centrifuged three times after ultrasonication to obtain a precipitate, and the precipitate is dissolved in sucrose water, and the precipitate is freeze-dried to obtain the squid ink nanoparticles CIMNP;
[0010] Cuttlefish ink nanoparticles were added to sodium alginate solution to obtain CIMNP@Alg solution, sodium alendronate was dissolved in calcium gluconate solution and then added to the CIMNP@Alg solution, and the CIMNP / Aln@Alg composite hydrogel was obtained after stirring.
[0011] As a preferred embodiment of the preparation method of the present invention, the cuttlefish ink nanoparticles are added into the sodium alginate solution, and the final concentration of the cuttlefish ink is 1 mg / mL.
[0012] As a preferred embodiment of the preparation method of the present invention, the concentration of the sucrose solution is 5%.
[0013] As a preferred embodiment of the preparation method of the present invention, the sodium alendronate is dissolved in a calcium gluconate solution and added to a CIMNP@Alg solution, wherein the final concentration of sodium alendronate in the system is 1 mmol, and the addition ratio of the sodium alendronate calcium gluconate mixed solution to the CIMNP@Alg solution is 1:3.
[0014] As a preferred embodiment of the preparation method of the present invention, the obtained suspension is centrifuged under the conditions of a temperature of 4°C, a centrifugal force of 2000 rpm, and a time of 10 min.
[0015] As a preferred embodiment of the preparation method of the present invention, the supernatant is taken and centrifuged continuously, wherein the centrifugation conditions are a temperature of 4° C., a centrifugal force of 14000 rpm, and a time of 10 min.
[0016] As a preferred embodiment of the preparation method of the present invention, the ultrasonic time is 15 minutes. As a preferred embodiment of the preparation method of the present invention, the average particle size of the squid ink nanoparticles is 220 nm, the PDI value is 0.059, the CIMNPs are evenly distributed, and the particles are negatively charged.
[0017] The potential value is -27.3mV.
[0018] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a CIMNP / Aln@Alg composite hydrogel to obtain a CIMNP / Aln@Alg hydrogel.
[0019] Another object of the present invention is to overcome the deficiencies in the prior art and provide a CIMNP / Aln@Alg hydrogel for use in bone repair.
[0020] Beneficial effects of the present invention:
[0021] (1) The present invention mixes squid ink nanoparticles with active oxygen scavenging properties and sodium alendronate with bone induction properties into an injectable alginate composite hydrogel by cationic crosslinking, and implants the composite hydrogel into a mouse skull defect model. The antioxidant properties and cell osteogenic properties of different groups of composite hydrogels are explored through in vitro cell experiments, and the bone repair properties of CIMNP / Aln@Alg composite hydrogel are explored through in vivo mouse skull defect repair experiments.
[0022] (2) The hydrogel in the present invention can provide a good scaffold structure for repair materials. The hydrogel is a three-dimensional hydrophilic network structure composed of cross-linked polymer chains. After absorbing water, it can remain undecomposed, simulate the natural tissue environment, and provide stable structural support for the defect site. The hydrogel material has good plasticity and freedom, can adapt to the shape and size of the bone defect site, ensure that the material fits tightly to the defect site, and provide a favorable microenvironment for the attachment and proliferation of bone cells.
[0023] (3) The hydrogel of the present invention has excellent mechanical properties. The hydrogel prepared by the present invention has good mechanical properties (such as compression modulus, storage modulus, etc.), and can better adapt to the mechanical environment of the bone defect site. It can provide a stable support and mechanical environment at the bone defect site, help prevent the graft from shifting or collapsing, and ensure the smooth progress of the bone regeneration process. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0025] Figure 1 These are SEM and TEM images of CIMNPs in Example 2 of the present invention.
[0026] Figure 2 This is the particle size and potential diagram in Example 2 of the present invention.
[0027] Figure 3 This is the FTIR spectrum analysis diagram in Example 2 of the present invention.
[0028] Figure 4 This is a diagram of the stability test results in Example 2 of the present invention.
[0029] Figure 5 This is the surface SEM image of the CIMNP / Aln@Alg composite hydrogel in Example 3 of the present invention.
[0030] Figure 6 This is a graph showing the swelling performance, degradation performance and porosity detection of the CIMNP / Aln@Alg composite hydrogel in Example 3 of the present invention.
[0031] Figure 7 This is the drug release diagram of CIMNP / Aln@Alg composite hydrogel in Example 3 of the present invention.
[0032] Figure 8 This is the rheological properties diagram of the CIMNP / Aln@Alg composite hydrogel in Example 3 of the present invention.
[0033] Fig. 9 This is a diagram of the free radical scavenging ability of the CIMNP / Aln@Alg composite hydrogel in Example 3 of the present invention.
[0034] Fig.10 This is a graph showing cell viability detected by MTT method using different gels with different concentrations of TBHP in Example 4 of the present invention.
[0035] Fig.11 This is a graph showing the detection of SOD, CAT, MDA and LDH contents in different gels in Example 4 of the present invention.
[0036] Fig.12 This is a diagram showing the effects of different gels in Example 4 of the present invention on oxidative stress-related genes in MC3T3-E1 cells.
[0037] Fig.13 This is a ROS fluorescence image of different gels in Example 4 of the present invention.
[0038] Fig.14 This is a graph showing the ability of different gels in Example 4 of the present invention to scavenge reactive oxygen species in MC3T3-E1 cells.
[0039] Fig.15 This is an ALP and ARS staining diagram of different groups of gels after continuous culture in Example 5 of the present invention.
[0040] Fig.16 The effect of different groups of gels on the expression of osteogenic-related genes in MC3T3-E1 cells in Example 5 of the present invention is shown in FIG.
[0041] Fig.17 This is a graph showing the levels of bone formation-related factors in serum detected by ELISA detection kit for different groups of gels in Example 5 of the present invention.
[0042] Fig.18 The in vivo micro-CT system scans of different groups of gels in Example 5 of the present invention.
[0043] Fig.19 This is a graph showing the effects of different groups of gel on bone density (BMD), bone volume fraction (BV / TV), and bone volume (BV) in Example 5 of the present invention. DETAILED DESCRIPTION
[0044] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0045] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0046] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0047] Unless otherwise specified, all raw materials used in the examples of the present invention are commercially available, as shown in Table 1 for details.
[0048] Table 1
[0049]
[0050]
[0051] Example 1
[0052] The present invention provides a method for preparing CIMNP / Aln@Alg hydrogel:
[0053] (1) Add distilled water to the cuttlefish ink sac, knead and stir until dissolved, and filter through gauze. Centrifuge the resulting suspension at 2000g for 5 minutes at 4°C to remove large particles. Take the supernatant and continue to centrifuge at 14000g for 10 minutes at 4°C. Then add a small amount of distilled water to the precipitate and stir to mix. After 100 Hz ultrasound for 10 minutes, repeat the centrifugation three times under the above conditions, dissolve the precipitate in 5% sucrose water, and freeze-dry to obtain cuttlefish ink nanoparticles.
[0054] (2) First, cuttlefish ink nanoparticles (CIMNPs) were added to sodium alginate solution (Alg concentration was 3 wt%), and sodium alendronate (Aln) was dissolved in calcium gluconate solution (3 wt%) and then added to CIMNP@Alg (volume ratio was 1:3), and stirred continuously for several minutes to obtain CIMNP / Aln@Alg composite hydrogel. The final concentration of CIMNP was 1 mg / mL, and the final concentration of Aln was 1 mmol.
[0055] Example 2
[0056] Characterization of Cuttlefish Ink Nanoparticles (CIMNPs):
[0057] Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to observe the prepared cuttlefish ink nanoparticles (CIMNPs).
[0058] like Figure 1 As shown, spherical particles with a particle size of about 150 nm and uniform size were successfully prepared.
[0059] (2) Particle size and potential analysis
[0060] According to the principle of dynamic light scattering, the particle size and PDI value of CIMNPs are detected based on the irregular movement of the liquid containing CIMNPs, which causes the fluctuation of the scattered light of the particles. Zeta potential is also one of the indicators of detection stability. The higher the absolute value of Zeta potential, the more stable the system.
[0061] like Figure 2 As shown, the average particle size of CIMNP was detected to be about 220nm, the PDI value was 0.059, the distribution of CIMNP was relatively uniform, and the Zeta potential showed that CIMNP was a negatively charged particle with a potential value of -27.3mV. The electrostatic repulsion between CIMNP particles maintained good stability and was not easy to aggregate.
[0062] (3) FTIR spectroscopy analysis
[0063] FTIR spectroscopy can be used to analyze the structure and chemical bonds of a substance, thereby inferring the structure and properties of a compound. Take a small amount of CIMNP solid sample and scan the sample using a near-infrared absorption spectrometer.
[0064] As spectrum Figure 3 It can be seen that at 1300cm -1 The carbonyl (C=O) stretching at 1500 cm -1 The amino (NH) bending vibration peak appears at 3200-3400cm -1 The stretching vibrations of the amino (NH) and hydroxyl (OH) groups occur at
[0065] (4) Stability
[0066] The CIMNPs were ultrasonically dispersed and dissolved in PBS solution and stored in a refrigerator at 4°C. A portion was extracted for stability testing for 14 consecutive days.
[0067] Figure 4 As shown, the particle size range of CIMNP is within 192 to 230 nm; the PDI range is within 0.4 to 0.7; and the Zeta potential value is within -25 to -31 mV, all of which have no significant changes. CIMNP is stable and evenly distributed in PBS solution at 4°C, without any dispersion destruction or coagulation.
[0068] The present invention successfully separated the cuttlefish ink nanoparticles (CIMNPs) from the cuttlefish ink sac by filtering, centrifuging and other methods. The CIMNPs are characterized to have an average particle size of about 220 nm, a PDI value of 0.059, a Zeta potential value of -27.3 mV, and are uniformly dispersed and stable spherical particles. The analysis of Fourier infrared spectroscopy shows that the CIMNPs contain melanin-like indole structures and rich antioxidant groups.
[0069] Example 3
[0070] Characterization of CIMNP / Aln@Alg composite hydrogel:
[0071] (1) SEM observation of composite hydrogel surface
[0072] like Figure 5 As shown in the figure, SEM shows that the gels in each group have loose porous structures and the surface of the gel is relatively smooth. The addition of CIMNPs and Aln 2+ The loose and porous structure of cross-linked Alg hydrogels did not change. EDS spectrum showed that the surface of CIMNP / Aln@Alg composite hydrogels was rich in calcium and phosphorus and was evenly distributed on the surface of the gel.
[0073] (2) Basic properties of gel
[0074] The gel swelling properties, degradation properties and porosity were tested.
[0075] Swelling: After the gel was successfully prepared, it was immersed in PBS solution, and the initial weight (Wi) and the weight after immersion for a period of time (Wt) were weighed to calculate the gel swelling ratio (Wt-Wi) / Wi×100%.
[0076] Degradation: The gel was weighed after freeze-drying, immersed in PBS, and placed at 37°C. After a certain interval (1, 3, 7, 14, and 28 days), it was taken out and freeze-dried again and weighed. The remaining weight was calculated. The gel initially degraded quickly, and after 28 days, it still retained about 25% of its weight.
[0077] Porosity: First, weigh the gels of different proportions in a dry state and record them as WS. Then pour anhydrous ethanol into a specific gravity bottle and record it as W1. The scaffold is completely immersed in anhydrous ethanol and the mass is recorded as W2. After removing the scaffold, the total mass of the specific gravity bottle and anhydrous ethanol is recorded as W3. The porosity P (%) is calculated by the following formula (1).
[0078]
[0079] according to Figure 6 As shown, the swelling of the gel basically reached stability after 4 hours, the gel initially degraded quickly, and still retained 20%-30% of its weight after 21 days. The porosity of each group of gels was similar and there was no significant difference.
[0080] (3) Drug release
[0081] Figure 7 As shown, the drug has a burst release in the first three days, while the release increases slowly in the later period, and the release can reach more than 60% within 14 days.
[0082] (4) Gel rheological properties
[0083] Figure 8 As shown, the storage modulus (G') of the hydrogels in all groups was higher than the loss modulus (G"), indicating that the solid hydrogel was successfully formed with a large G' value, which could provide appropriate mechanical strength for bone repair.
[0084] (5) Gel free radical scavenging ability
[0085] Methods: CIMNP / Aln@Alg composite gels with different final concentrations were prepared and incubated with DPPH (0.1 mmol, 95% ethanol) for 6 h in the dark. Centrifuged at 12000 rpm for 5 min, 100 μL of supernatant was added to a 96-well plate, and the absorbance at 517 nm was measured by an ELISA reader.
[0086] Fig. 9As shown in the figure, the composite gel has a scavenging effect on free radicals such as DPPH and ABTS, and the scavenging ability of the composite gel containing different concentrations of CIMNPs shows a dose-dependent trend.
[0087] Comparative Example 1 (Alg)
[0088] The difference from Example 1 is that this group of gels is a simple matrix gel without any drug. It does not contain sodium alendronate and cuttlefish ink nanoparticles. The preparation method is to add calcium gluconate solution (3wt%) to Alg solution (Alg concentration is 3wt%) (volume ratio is 1:3), and stir continuously for several minutes to obtain Alg hydrogel.
[0089] Comparative Example 4 (Aln@Alg)
[0090] The difference from Example 1 is that the drug control group does not contain squid ink nanoparticles. Sodium alendronate (Aln) was dissolved in calcium gluconate solution (3wt%) and then added to Alg solution (Alg concentration was 3wt%) (volume ratio was 1:3), and stirred continuously for several minutes to obtain Aln@Alg composite hydrogel. The final concentration of Aln was 1mmol.
[0091] Comparative Example 5 (CIMNP@Alg)
[0092] The difference from Example 1 is that the pure nanoparticle control group does not contain sodium alendronate. The preparation method is to first add cuttlefish ink nanoparticles (CIMNP) to sodium alginate solution (Alg concentration is 3wt%), add calcium gluconate solution (3wt%) to CIMNP@Alg (volume ratio is 1:3), and stir continuously for several minutes to obtain CIMNP@Alg composite hydrogel. The final concentration of CIMNP is 1mg / mL.
[0093] Example 4
[0094] Antioxidant capacity detection of CIMNP / Aln@Alg composite hydrogel:
[0095] Firstly, tert-butyl hydroperoxide (TBHP) was used to induce MC3T3-E1 cells to establish an oxidative stress model. After different groups of gels were co-incubated with TBHP, the effects of gels on oxidative damage were studied by measuring cell viability, levels of oxidative stress-related factors, and reactive oxygen species (ROS) generation.
[0096] MTT assay for cell viability:
[0097] After the cells were plated in 96-well plates and incubated overnight, different concentrations of drugs were added for treatment. After 0.5 mg / mL MTT solution was added to each well and incubated for 4 h, 200 μL DMSO was added to each well. After 10 min, the absorbance was detected at 570 nm with a microplate reader.
[0098] Effects of gel on MC3T3-E1 cell activity:
[0099] After the different groups of gels were incubated with cells, the cell viability was detected by MTT method.
[0100] (1) Establishment of MC3T3-E1 cell oxidative damage model
[0101] After the cells were treated with different concentrations of TBHP (0, 30, 40, 50, 100, 200, 400, 600, 800 μmol) for 4 h, the cell survival rate was detected by the MTT method.
[0102] according to Fig.10 As shown, after 30 μmol TBHP acted on MC3T3-E1 cells for 4 hours, the cell viability decreased to 80%, which was consistent with the establishment of the oxidative stress model. When different groups of gels acted on cells together, the cell viability of the gel containing CIMNP group increased, and the difference was significant compared with the model group, which proved that the gel containing CIMNP group can effectively reduce the oxidative stress of MC3T3-E1 cells induced by TBHP.
[0103] (2) Detection of oxidation-related factor content
[0104] After the cells were co-treated with each group of gels and TBHP, the contents of SOD, CAT, MDA and LDH were detected using different kits.
[0105] according to Fig.11 As shown in the figure, the antioxidant effect of the gel was further explored by measuring the antioxidant enzyme activity and lipid peroxides of the MC3T3-E1 cells treated with each group of gel under the oxidative stress model. The contents of SOD, CAT, MDA, and LDH in each group were calculated by WST-8 method, colorimetry, and microplate method. The contents of SOD and CAT in the model group decreased significantly, and the contents of MDA and LDH increased significantly; after treatment with the gel containing the CIMNP group, SOD, CAT, MDA, and LDH recovered, while the gel group without CIMNP had no obvious recovery trend. It can be seen that the gel in the CIMNP group has a significant inhibitory effect on the oxidative damage of MC3T3-E1 cells induced by TBHP.
[0106] (3) Effects of gel on oxidation-related genes
[0107] To further explore the effect of the gel on MC3T3-E1 cells, real-time quantitative polymerase chain reaction (q-PCR) analysis was used to evaluate the levels of oxidative stress-related genes in MC3T3-E1 cells.
[0108] like Fig.12As shown in the results, it was found that after TBHP treatment, the gene expression level in the model group was significantly reduced, while after the addition of CIMNP-containing gel, the gene expression level was upregulated, proving that CIMNP-containing gel can effectively upregulate the expression of anti-oxidative stress-related genes (NQO1, GST, GSH, HO-1) in MC3T3-E1 cells under the ROS microenvironment and the difference was significant.
[0109] (4) Ability of CIMNP / Aln@Alg hydrogel to scavenge reactive oxygen species in MC3T3-E1 cells
[0110] In order to detect the ability of CIMNP / Aln@Alg hydrogel to scavenge ROS of MC3T3-E1 cells, this experiment used fluorescence microscopy, flow cytometry and other methods to study the ROS level of MC3T3-E1 cells. MC3T3-E1 cells were inoculated, and after overnight incubation, different groups of gels were added for pretreatment for 24 hours, and TBHP was added for treatment for 4 hours. Serum-free medium containing 2,7-dichlorodihydrofluorescein diacetate (DCFH-DA) was added and incubated for 30 minutes. After washing with serum-free medium, ROS fluorescence was observed under a fluorescence microscope. Cells were collected and detected by flow cytometry.
[0111] Fig.13 and 14 As shown, the gels without CIMNPs (Alg, Aln@Alg) showed the same green fluorescence intensity as the TBHP model group, while the green fluorescence intensity decreased after the addition of the gel containing CIMNPs. The results show that CIMNPs have the ability to scavenge ROS in the composite gel, and after the addition of the gel containing CIMNPs, the cellular ROS level is close to that of the cell group without TBHP induction, which once again proves that CIMNPs have a strong ability to scavenge intracellular ROS. Flow cytometry showed the same results as fluorescence microscopy. Since the gels without CIMNPs (Alg, Aln@Alg) do not have the ability to scavenge ROS, the fluorescence intensity values are close to those of the TBHP model group, and due to the ROS scavenging ability of CIMNPs, the fluorescence intensity values of the CIMNP@Alg and CIMNP / Aln@Alg gel groups are close to those of the control group.
[0112] CIMNP / Aln@Alg gel has the ability to scavenge ROS in MC3T3-E1 cells, and it is proved that the composite gel mainly exerts its ROS scavenging function through the CIMNPs contained therein.
[0113] Example 5
[0114] In vitro osteogenic ability test of CIMNP / Aln@Alg composite hydrogel:
[0115] (1) ALP and ARS staining
[0116] MC3T3-E1 cells, as osteoblast precursor cells, can differentiate into osteoblasts after adding induction agents and participate in the body's bone formation process. Alkaline phosphatase (ALP) and Alizarin red (ARS) staining can show the osteogenic differentiation of MC3T3-E1 cells.
[0117] After MC3T3-E1 cells were plated, different groups of gels and osteogenic induction medium were added, and ALP and ARS staining were performed after continuous culture for 7 or 21 days, respectively.
[0118] The results are as follows Fig.15 As shown, compared with the control group, the addition of gel containing sodium alendronate (Aln) can effectively promote the osteogenic differentiation of MC3T3-E1 cells.
[0119] (2) Expression of osteogenesis-related genes
[0120] To further explore the effect of gel on the osteogenic function of MC3T3-E1 cells, real-time quantitative polymerase chain reaction (q-PCR) analysis was used to evaluate the levels of osteogenesis-related genes in MC3T3-E1 cells.
[0121] like Fig.16 As shown, compared with other groups, the levels of bone formation-related genes in the group containing Aln gel showed a significant upregulation trend, indicating that Aln-containing gel has a stronger promoting effect on bone formation.
[0122] Example 6
[0123] In vivo osteogenesis experiment of CIMNP / Aln@Alg composite hydrogel:
[0124] Eight-week-old female Bal / bc mice (Center of Comparative Medicine, Yangzhou University) weighing more than 20 g were selected and randomly divided into a control group, an Alg group, an Aln@Alg group, a CIMNP@Alg group, and a CIMNP / Aln@Alg group. A 3-mm-diameter trephine was used to form a 3-mm full-thickness defect in the skull of each mouse. The hydrogel was then injected into the defect of the experimental group, and the control group was not treated. The mice were killed after 8 weeks, and the specimens were collected for Micro-CT analysis.
[0125] (1) ELISA detection of serum bone formation related indicators
[0126] Blood was collected from mice, and serum was obtained by coagulation. The levels of bone formation-related factors in the serum were detected using an ELISA detection kit.
[0127] Fig.17 As shown, the levels of osteogenic-related factors in the serum of the drug (Aln) group showed an upward trend compared with the blank control group and the difference was significant.
[0128] (2) Micro-CT bone formation related indicators
[0129] After the mice were anesthetized, they were scanned with an in vivo micro-CT system to evaluate the formation of new bone in the defect area, including bone density (BMD), volume fraction (BV / TV), and bone volume (BV).
[0130] Fig.18 and 19 As shown in the figure, 10 weeks after the implantation of each group of gels, the rat skull specimens were collected and three-dimensional reconstruction data were obtained by micro-computed tomography (Micro-CT). Compared with the blank group, Alg group and CIMNP@Alg group, more new bone tissue, maximum bone volume fraction (BV / TV) and bone healing area appeared in the bone defect area treated by Aln@Alg group and CIMNP / Aln@Alg gel group, which confirmed that Aln can effectively promote bone regeneration in vivo, and combined treatment with CIMNP can promote bone regeneration more efficiently.
[0131] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A method for preparing a CIMNP / Aln@Alg composite hydrogel, characterized in that: include, The squid ink sac is kneaded and stirred with water until dissolved, and then filtered to obtain a suspension; the obtained suspension is centrifuged and the supernatant is taken and further centrifuged, water is added to the precipitate and stirred, and the precipitate is repeatedly centrifuged three times after ultrasonication to obtain a precipitate, and the precipitate is dissolved in sucrose water, and the precipitate is freeze-dried to obtain the squid ink nanoparticles CIMNP; Cuttlefish ink nanoparticles were added to sodium alginate solution to obtain CIMNP@Alg solution, sodium alendronate was dissolved in calcium gluconate solution and then added to the CIMNP@Alg solution, and the CIMNP / Aln@Alg composite hydrogel was obtained after stirring.
2. The preparation method according to claim 1, characterized in that: The squid ink nanoparticles are added to the sodium alginate solution, and the final concentration of the squid ink is 1 mg / mL.
3. The preparation method according to claim 2, characterized in that: The concentration of the sucrose solution is 5%.
4. The preparation method according to claim 1, characterized in that: The sodium alendronate is dissolved in a calcium gluconate solution and added to a CIMNP@Alg solution, wherein the final concentration of the sodium alendronate in the system is 1 mmol, and the addition ratio of the sodium alendronate calcium gluconate mixed solution to the CIMNP@Alg solution is 1:
3.
5. The preparation method according to claim 1, characterized in that: The obtained suspension is centrifuged, wherein the centrifugal conditions are a temperature of 4° C., a centrifugal force of 2000 rpm, and a time of 10 min.
6. The preparation method according to claim 1, characterized in that: The supernatant was taken and centrifuged continuously, wherein the centrifugation conditions were temperature of 4° C., centrifugal force of 14000 rpm, and time of 10 min.
7. The preparation method according to claim 1, characterized in that: The ultrasonic time is 15 min.
8. The preparation method according to claim 2, characterized in that: The average particle size of the squid ink nanoparticles is 220 nm, the PDI value is 0.059, the CIMNPs are evenly distributed, and the particles have a negative charge and a potential value of -27.3 mV.
9. CIMNP / Aln@Alg hydrogel prepared by the preparation method of claims 1 to 8.
10. Use of the CIMNP / Aln@Alg hydrogel as claimed in claim 9 in bone repair.